The war of the worlds - Wells, H. G. (Herbert George), 1866-1946 ([Boston, Mass] : Thomson Heinle, 2007)
Great cities destroyed--people fleeing in panic--the countryside in ruins. A burst of flame from Mars heads toward the earth, and a strange ship, unlike anything ever seen here, lands. Soon, it devours everything in its path, people and buildings alike. It is unstoppable. Mankind is in the greatest danger in all its history
Title from container
Keywords: Imaginary wars and battles -- Fiction; Space warfare -- Fiction; Mars (Planet) -- Fiction